QARAQALPAQ TILIN OQÍTÍWDA OQÍWSHÍLARDÍŃ SÓZLIK BAYLÍǴÍN RAWAJLANDÍRÍW JOLLARÍ - Allaniyazova, Sh. (SCIENCE and SOCIETY, 2024)
In this article, there are opinions about the ways of improving the vocabulary of students in teaching the Karakalpak language, molding and improving clear speaking skills, improving the students’ ability of thinking freely, the importance of dictionaries, and the role of books in improving the vocabulary of students.